Correction: Fabrication of poly-crystalline Si-based Mie resonators via amorphous Si on SiO2 dewetting. Issue 14 (18th March 2016) - Naffouti, Meher; David, Thomas; Benkouider, Abdelmalek; Favre, Luc; Ronda, Antoine; Berbezier, Isabelle; Bidault, Sebastien; Bonod, Nicolas; Abbarchi, Marco
Abstract : Correction for 'Fabrication of poly-crystalline Si-based Mie resonators via amorphous Si on SiO2 dewetting' by Meher Naffouti, et al., Nanoscale, 2016, 8, 2844–2849.